Distance Education and the Issue of Equity Online: Exploring the Perspectives of Rural Aboriginal Students - Gibb, Heather (The Australian Journal of Indigenous Education, 2006)
Abstract This paper explores Aboriginal perspectives of tertiary education “online” from rural and remote community locations in New South Wales. It does so within a frame of enquiry as to how neo-liberal educational policy reforms are impacting on equity issues in distance education “online”. Accounts from Aboriginal university students in health point to a range of tensions between changes brought about by the reform in relation to student subjectivity and university governance, and culturally preferred ways of learning for many Aboriginal people. The paper offers suggestions for how these forms of educational governance can be reconciled with educational support needs of remote Aboriginal learners.